Engaging young readers : promoting achievement and motivation - Baker, Linda; Dreher, Mariam Jean; Guthrie, John T. (Solving problems in the teaching of literacy, 2000)
This volume demonstrates how promoting children's engagement with reading can greatly enhance reading achievement. From leading literacy researchers and educators, the book illuminates what a child needs to become an engaged reader and presents a set of instructional principles designed to facilitate this goal. Helping teachers offer a coordinated emphasis on competence and motivation in reading instruction, chapters blend research evidence with practical recommendations. Topics covered include ways to provide children with a good foundation at the word level, help if they are in trouble, ample time and materials for reading, opportunities to share in a community of learners, instruction that is coherent, motivating, and responsive to each child's strengths and weaknesses, school-wide coordination of instruction, and continuities between home and school.